PENGARUH LKPD BERBASIS INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SEKOLAH DASAR - Siti Nurjanah; Muhammad Arya Wirayuda; Deviyanti Pangestu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem of this research was the low critical thinking ability in the learning of science in grade V elementary school students because educators have not maximized the use of teaching materials. The purpose of this study was to determine the effect of worksheet based on guided inquiry on the critical thinking ability of science in grade V elementary school students. The research method was a quasi-experimental method with a one-group pretest-posttest design. The research sample consisted of 21 class students. Data collection techniques used test techniques. The results showed that there was a significant effect on the use of worksheetvbased on guided inquiry on the critical thinking ability of science in grade V students of SD Negeri 4 Metro Utara.